Pengembangan Pendidikan Kecakapan Hidup di SMK Al-Furqon Jambesari Darus Sholah Bondowos: Development of Life Skills Education at Al-Furqon Vocational School Jambesari Darus Sholah, Bondowoso - Syamsul Syamsul (Fenomena, 2013)
Education is a conscious and deliberate effort to create a learning atmosphere and process so that learners actively develop their potential to possess spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed for themselves, society, nation, and state. The development of life skills education, which includes cognitive, affective, and psychomotor skills, is an activity aimed at shaping students' creativity. Pendidikan merupakan upaya sadar dan terencana untuk menciptakan suasana belajar serta proses pembelajaran agar peserta didik secara aktif mengembangkan potensi dirinya, sehingga memiliki kekuatan spiritual keagamaan, pengendalian diri, kepribadian, kecerdasan, akhlak mulia, serta keterampilan yang diperlukan bagi dirinya, masyarakat, bangsa, dan negara. Pengembangan pendidikan kecakapan hidup yang mencakup keterampilan kognitif, afektif, dan psikomotor merupakan kegiatan dalam membentuk kreativitas siswa.